Xylitol and its usage in ENT practice. Issue 7 (July 2014) - Sakallioğlu, Ö; Güvenç, I Adadan; Cingi, C
Abstract Background: Xylitol is a five-carbon sugar alcohol. Natural sources of xylitol include plums, strawberries and raspberries. Xylitol is commercially available in chewing gums, lozenges, syrups, nasal sprays, toothpastes, mouthwashes and other products in some countries. It has gained relative prominence in the past decade as a naturally occurring antibacterial agent. Objective: A review of contemporary literature was conducted to evaluate the efficacy of xylitol usage in ENT practice. Method: The English-language literature was searched using the following terms: xylitol, otitis media, nasal, sinusitis, dental caries and preventive therapy. The articles identified were included in this review. Results: Xylitol has no antibacterial properties of its own; rather, it appears to enhance the body's own innate immunity. Xylitol has anti-adhesive effects on micro-organisms like Streptococcus pneumoniae and Streptococcus mutans, inhibiting their growth. Xylitol has already been used for preventing otitis media, rhinosinusitis and dental caries. The worldwide spread of drug-resistant strains of pneumococci substantiates the need for new approaches to prevent ENT-related infectious diseases. Conclusion: Xylitol may be a promising agent for this purpose in ENT practice, but further experimental and clinical studies are required.